Reappraising political theory : revisionist studies in the history of political thought - Ball, Terence (Oxford University Press, 1994)
In this book, Terence Ball injects new life into the great works of political theory. By suggesting new ways of looking at the 'classic' texts, he shows how they can offer compelling answers to the problems we face today.